Rate of change of total column ozone and monsoon rainfall - A co-variation with the variable component of 10.7 cm solar flux during pre-monsoon period - MIDYA, S. K.; SAHA, U. (MAUSAM, 2011)
A critical analysis is done on the variation of the rate of change of Total Column Ozone (TCO) over Dum Dum (22° 38 N, 88° 26 E) and Total Monsoon Rainfall over Gangetic West Bengal with the variable component of 10.7 cm solar flux during different seasons for the period 1997- 2005. An anti-correlation is observed between the variable component with the rate of change of TCO during the pre-monsoon and monsoon period and significant positive correlations during the post-monsoon and winter seasons. Quite insignificant positive correlations are observed between the variable component and Total Monsoon Rainfall during different seasons for this period. A co-variation is observed with the increase in the variable component of 10.7 cm solar flux throughout the period of study only during the pre-monsoon season. Possible explanations are also presented.